A Mechanism for Slow Electrostatic Solitary Waves in the Earth’s Plasma Sheet - Gurbax Singh Lakhina; Satyavir Singh (Plasma)
An analysis of the Magnetospheric Multiscale (MMS) spacecraft data shows the presence of slow electrostatic solitary waves (SESWs) in the Earth’s plasma sheet, which have been interpreted as slow electron holes (SEHs). An alternative mechanism based on slow ion-acoustic solitons is proposed for these SESWs. The SESWs are observed in the region where double humped ion distributions and hot electrons co-exist. Our theoretical model considers the plasma in the SESW region to consist of hot electrons with a vortex distribution, core Maxwellian protons drifting parallel to the magnetic field, B and beam protons drifting anti-parallel to B. Parallel propagating nonlinear ion-acoustic waves are studied using the Sagdeev pseudopotential technique. The analysis yields four types of modes, namely, two slow ion-acoustic (SIA1 and SIA2) solitons and two fast ion-acoustic (FIA1 and FIA2) solitons. All solitons have positive potentials. Except the FIA1 solitons which propagate parallel to B; the other three types propagate anti-parallel to B. Good agreement is found between the amplitudes of electrostatic potential, the electric field, the widths and speed of SIA1 and SIA2 solitons, and the observed properties of SESWs by the MMS spacecraft.